The Reflection of Peace Principles In Muhammad Shaybani's Works - Juraev, Shukrullo (Jurnal Pendidikan Islam, 2024)
This article discusses the principles aimed at preserving peace in the works of Muhammad Shaybani, a prominent figure in the Hanafi school of thought. The works of Muhammad Shaybani are recognized as authoritative sources of the Hanafi school by its scholars. Notably, the scholar's work “As-Siyar Al-Kabir” stands out as it is directed towards regulating international relations arising between representatives of different religions in times of war and peace. It is known that Islam, by its very nature, is a religion of peace. It urges people to strive for peace and stability, to eliminate various discord and animosity. Indeed, peace constitutes the foundation of the Islamic religion. However, today, representatives of extremist sects misinterpret the principles of war and peace mentioned in the Qur'an and Hadiths, attempting to portray Islam as a religion of war. The article presents the views of prominent scholars of the Hanafi school on the preservation of peace in Islam. Additionally, it elucidates the essence of the rules concerning war and peace presented in the Qur'an and Hadiths. Especially, the views of Islamic scholars on the concept of “jihad,” which is currently being distorted and misinterpreted by radical individuals, are included.